Dhakaiyas on the move - Khatun, Hafiza (Dhaka : Academic Press and Publishers, 2003)
Case study with reference to the dwellers of Dhaka City, Bangladesh.
Includes bibliographical references (p. [150]-160).
Keywords: Residential mobility -- Bangladesh -- Dhaka -- Case studies; City dwellers -- Bangladesh -- Dhaka -- Case studies; Dhaka (Bangladesh) -- Population -- Case studies